The role of self-control on peer attachment and internet addiction - Buntaran, Firman Alamsyah Ario; Aprianti, Melani; Sabir, Shmad (JURNAL SPIRITS, 2024)
There has been an increase in the prevalence of internet addiction among adolescents in recent years. It is known that self-control and attachment are protective factors against various maladaptive behaviors in adolescents. In middle adolescence, close friends become the main source of intimacy and openness and are the main providers of emotional and social support. However, there has been no research in Indonesia that assesses the role of the protective factor of self-control as an introductory factor of various maladaptive behaviors. The purpose of this study was to assess the role of self-control as an intermediary factor in the relationship between peer attachment and internet addiction in 114 high school students. Mediation test using Macro Process and Sobel calculation, the results of the mediation test showed that self-control can fully mediate the relationship between peer attachment and internet addiction. These findings provide important suggestions for parents and schools to be able to provide interventions regarding the importance of self-control and the meaning of peer attachment among students